Diurnal variation in transpiration in rice and wheat plants grown in sand and sandy soil under channel irrigation system - Rahman, Md Khalilur (Dhaka University Journal of Biological Sciences, 2015)
Transpiration loss of water of rice and wheat plants at different times of the day grown in sand and sandy soil in specially design earthen pots was studied. The highest plateau of transpiration loss was observed at 14:30 hour for both the crops. The results did not vary significantly (p = 0.05). Dhaka Univ. J. Biol. Sci. 24(2): 215-218, 2015 (July)